Assessment of the technology adoption and implementation of the OpenClassroom Project an examination of the adoption and operating model of the open OpenClassroom Project: a technology based program focused on enhancing classroom learning in the Philippines - Concepcion, Rafael Roman D. (University of the Philippines Diliman, 2013)
This report attempts to examine and evaluate the operating model of the OpenClassroom Project, a technology-based education program that focuses on helping improve K12 public school learning, from a technology management perspective. The report also takes into account the context of working within the local public school system environment and the unique challenges within it. The report focuses on the following primary areas: Documenting and examining the overall program implementation and issues that were encountered during the process. Examining and addressing technology adoption issues that occurred during the actual program implementation. Determining outcomes and gauging the effectiveness of the program based on qualitative and quantitative data gathered during program implementation. Gauging technology acceptance level of the teacher, facilitator, and students who were direct users of the system within the program. Providing a set of recommendations for future implementation and expansion to help improve the program in general from a technology management perspective. The OpenClassroom team partnered with the Wishcraft foundation and Dr. Sixto Elementary School in Pasig in order to implement its pilot activity. The team successfully ran and implemented the pilot program from October 2012 to January 2013 with twenty (20) fifth grade participants going through six (6) separate modules on computer usage and mathematics. Observations, performance data, and interviews with various stakeholders were used as the primary sources of information for this report. The examination and evaluation methods used for this report follow the Technology Acceptance Model (TAM) by Fred Davis (1989) as a primary guide for measuring the overall success of the project qualitatively from a technology management standpoint. The questions that were used when interviewing participants were partially derived from the original model with modifications to match the context of the application. The primary issues that were encountered are summarized as follows : Funding- since the program takes place within the public school environment, an outside partner was brought in to help shoulder the costs of the program implementation. Administrative support - the support from the Principal and Vice-Principal in terms of endorsing the program to the rest of the staff. Resource availability - this includes the availability and operational state of the location, actual computer units (as well as operating systems), and other physical resources used for the actual program implementation. Technical proficiency - this includes how comfortable the facilitator (teacher) and students were in the basic use of computers and the systems used by the program. Management and deployment - tracks the actual implementation of the program and how the actual systems performed, what bugs were encountered, and how different real-time problems were solved (ex. system bugs or user-generated problems during actual use). Results measurement - deals with issues related to gathering and measuring performance data within the constraints of the program environment. In terms of administrative support and general acceptance, the project was deemed a success by the administration, facilitators and students in the sense that the program made use of existing school computers that were underutilized and not fully integrated into regular educational workflow, the students were exposed to a new way of learning school lessons through the use of rich media, there was a general sense of enthusiasm about implementing a technology-based program, and there were tangible results based on the performances of the students themselves. In terms of resource availability, the program team encountered a number of logistical issues in the initial setup and actual use of the physical equipment. A technical assessment was performed on the state and capability of all the physical resources that were to be used by the program including the facility itself and the actual computers. It was this assessment that determined the method for deployment of the program - the learning system itself was installed on each computer instead of delivering the lessons over to Internet to work around issues of networking and connectivity. During the program itself, minor issues such as user-generated problems with the system and hardware glitches were also encountered. The presence of a member of the program team for over eighty percent (80 percent) of the sessions helped ease the potential burden of addressing technical concerns. Regarding the technical proficiency of the facilitators and teachers, additional training was needed where the program team went through the initial modules step-by-step in order to help them navigate through the program initially. Minor difficulties were also encountered during the actual implementation such as program crashes or equipment malfunction (sometimes due to students' tinkering) which led to the need for periodic external support during the actual sessions. In terms of the actual data gathered for student performance during the activity, results varied depending on the existing academic performance and level of the students. Students in the school are currently grouped into classes based on their performance for the previous year with section one (1) being the best performing group and section (4) being the weakest performing group. 20 students were selected from sections 2-4 to participate. It was observed that students from section 3 made the most significant gains (in terms of quiz score and general improvement from session to session). This study made use of the Technology Acceptance Model by Davis (1989), particularly the concepts of perceived usefulness and perceived ease of use, as a general guide for determining the general attitudes of the teacher, facilitators, and students towards the technology used for the program. To get the feedback from each of these stakeholders an interview was held with the teacher and facilitator regarding their experiences with the technology after the program concluded and the students were asked on the spot at random during the actual program implementation regarding their feelings towards using computers in learning their formal schooling projects. Most of the attention was focused on the feedback of the teacher since she was the person who handled the general pace and flow of the program. The main points the teacher made regarding the ease of use include that after the initial training and practice with the system itself (and since the modules were intentionally designed to be delivered following the same flow and format) was that it was an easy to use technology since it was a familiar one (the system was delivered in the same way one uses a web browser- only with bigger and more colorful images, buttons and fonts). The problems the teacher encountered were primarily in bugs that were left in the system but were eventually fixed by the end of the program. The facilitators noted the simplicity and colorfulness of the modules themselves as the main drivers for their ease of use. As for the students, their general response was that they were happy to be using computers for learning in place of the standard classroom lecture. Regarding perceived usefulness, the teacher noted that it would be nice to incorporate the system into the regular course workflow, although she also noted that doing so would be difficult given the relative lack of physical resources and the general attitudes of the other less-technically inclined faculty. For the facilitators, who were also parents of some of the students, they showed particular interest in taking home the system and using it on their own home computers for review purposes. The students, across the board, felt the program was useful in helping them learn their lessons. The end result however, in terms of improved academic performance due to program participation, were mixed due to several other factors that came into play such as attendance, reading level and arithmetic proficiency. Going forward, in order for the program to continue expanding, the deployment module needs to be examined in terms of the logistics and technologies used for the program, the commitment from the incoming principal needs to be secured to ensure continuity and support, a larger group of teachers need to be educated on the program's significance and actual use, a resource needs to be assigned to help facilitate future programs as well maintain existing equipment and software. Resource availability, technical proficiency (or at least responsiveness of participants to learn), deployment, maintenance and data collection will also continue to be the primary issues for future implementation efforts, particularly those on a larger scale. These issues can be addressed by improving planning and preparation methods before the actual implementation, open and frequent two-way communication between the program team and target school, and better standardization of all the methods and applications used throughout the program.